THE PROBLEMS OF STOCK MARKET TURNOVER - Kakhramon Chinkulov (Journals Park Publishing, 2023)
The article analyzes the volume of the total issue of stocks and the dynamics of exchange turnover, compares the share of exchange turnover in GDP in Uzbekistan and abroad, indicates the reason for the low liquidity of the exchange, developed scientific and practical conclusions and proposals.
Keywords: stocks, joint-stock company, IPO, SPO, issue, share capital, stock market, securities market, financial market, exchange turnover.